2012
DOI: 10.1002/app.37757
|View full text |Cite
|
Sign up to set email alerts
|

Production of modified clays and their use in polypropylene‐based nanocomposites

Abstract: The use of modified bentonite as a reinforcement in polypropylene (PP)/organoclay/maleic anhydride grafted polypropylene (MAPP) nanocomposites was investigated. The modified bentonites (organoclays) were prepared from raw (unpurified) bentonite (RB) and two quaternary ammonium salts with long alkyl tails: hexadecyl trimethyl ammonium bromide [HDA][Br] and tetrakisdecyl ammonium bromide [TKA] [Br]. The ternary composites were produced by using a corotating twin screw extruder, followed by injection molding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The solution of 0.1 N AgNO 3 was used to test whether the paste contains the chloride ion or not. Lastly, the wet paste was dried for one day at 100°C in an oven, and then the dried paste was ground in the mortar .…”
Section: Methodsmentioning
confidence: 99%
“…The solution of 0.1 N AgNO 3 was used to test whether the paste contains the chloride ion or not. Lastly, the wet paste was dried for one day at 100°C in an oven, and then the dried paste was ground in the mortar .…”
Section: Methodsmentioning
confidence: 99%
“…Bentonite is also often applied as a filler for both thermoplastic, thermoset polymer composites, and elastomers [30][31][32][33][34][35][36]. Since bentonite is hydrophilic, it is often not compatible with most polymers and can be chemically modified to render its surface to be more hydrophobic [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Since bentonite is hydrophilic, it is often not compatible with most polymers and can be chemically modified to render its surface to be more hydrophobic [33,35]. Additionally, chemical modification of bentonite becomes necessary to increase the polarity of the polymer matrix by grafting polar groups [36]. The improvement of the interfacial bonding between the hydrophilic fillers and the hydrophobic polypropylene matrix has also been an essential issue in the research field because the interfacial adhesion between the filler and polypropylene plays an important role in determining the properties of composites.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that most of the formations faced in petroleum exploitation are shale formations . Clay minerals, as a major mineral of shale formations, may occur hydration, swelling and further migration when contacted with the external liquid, which is the main factor causing formation permeability damages and downhole accidents . At present, using clay stabilizers has become one of the most common methods to prevent or weaken the hydration …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that ionic liquid (trihexyl tetradecylphosphonium tetrafluoroborate) was inserted into montmorillonite (MMT), as a catalyst, and could be used under high temperature (up to 150°C), which might signify that ionic liquid may be a promising small molecule for combing with polymer because of its capability to embed clay layers . And Sandra L. detailed the evaluation of two ionic liquids as KCl substitutes . Nevertheless, polymer combining with ionic liquid, hasn't been reported as clay stabilizers in oil field chemicals so far.…”
Section: Introductionmentioning
confidence: 99%